2017
DOI: 10.1007/s10142-017-0582-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt-stress on gene expression in citrus roots revealed by RNA-seq

Abstract: Citrus, as one of the most economically important fruits worldwide, is adversely affected by salinity stress. However, its molecular mechanisms underlying salinity tolerance are still not clear. In this study, next-generation RNA-seq technology was applied to analyze the gene expression profiling of citrus roots at 3 time points over a 24-h period of salt treatment. A total of 1831 differentially expressed genes (DEGs) were identified. Among them, 1195 and 1090 DEGs were found at 4 and 24 h, of which 454 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 86 publications
3
30
0
Order By: Relevance
“…This can be done by comparing the transcriptome of tolerant and sensitive species in response to salinity (Gong et al , 2005). Transcriptomics approaches have been applied to identify salinity-induced differentially expressed genes (DEGs) in roots for a range of species (Senadheera et al , 2009; Cotsaftis et al , 2011; Zahaf et al , 2012; Geng et al , 2013; Xie et al , 2018). However, most of these results were conducted at the whole-root level, with only a few studies (Dinneny et al , 2008; Gruber et al , 2009; Hill et al , 2016) investigating the response of the transcriptome to salinity in different root zones.…”
Section: Introductionmentioning
confidence: 99%
“…This can be done by comparing the transcriptome of tolerant and sensitive species in response to salinity (Gong et al , 2005). Transcriptomics approaches have been applied to identify salinity-induced differentially expressed genes (DEGs) in roots for a range of species (Senadheera et al , 2009; Cotsaftis et al , 2011; Zahaf et al , 2012; Geng et al , 2013; Xie et al , 2018). However, most of these results were conducted at the whole-root level, with only a few studies (Dinneny et al , 2008; Gruber et al , 2009; Hill et al , 2016) investigating the response of the transcriptome to salinity in different root zones.…”
Section: Introductionmentioning
confidence: 99%
“…In other plants, it has been well demonstrated that the expression of cell wall-related genes was significantly downregulated under salt condition [62,63]. Accordingly, in our study, we found that as many as 62 DE genes involved in cell wall pathways, including six subgroups of cell wall protein, cellulose synthesis, cell wall precursor synthesis, cell wall modification, cell wall pectin esterase, and cell wall degradation, were dramatically downregulated by salt (Figure 6), which might explain why the growth of duckweed was greatly inhibited under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…For example, RNA-seq analysis of two citrus roots samples treated with salt stress for 4 and 24 h led to the identification of 454 overlapped differentially expressed genes (DEGs) [ 22 ]. Functional categorization of these DEGs revealed that some of them were involved in the salt overly sensitive (SOS) and ROS signaling pathways [ 22 ]. In addition, other DEGs coding for a variety of transcription factors (TF S ) have been identified, including WRKY, NAC, MYB, AP2/ERF, BZIP, which were verified as key regulators in salt or other stress signaling pathways in model plants and some crop plants [ 22 ].…”
Section: Introductionmentioning
confidence: 99%